THE EFFECT OF LEVERAGE ON PROFITABILITY WITH ACTIVITY RATIO AS AN INTERVENING VARIABLE IN PROPERTY AND REAL ESTATE COMPANIES LISTED ON THE IDX 2017 - 2021 PERIOD - Pasya, Syafira Meilia; Mahmudi, Bambang; Suryani, Emma; Rosyid, Abdul; Mulyani, Ana Susi (Management Science Research Journal, 2023)
Financial performance is an illustration of the company's success achievement can be interpreted as the results that have been achieved on various activities that have been carried out. This study aims to determine whether debt policy affects profitability with Activity Rattio as an intervening variable. The population of this study are Real Estate and Property companies listed on the Indonesia Stock Exchange for the period 2017-2021. The sampling in this study uses the Purposive Sampling method. Analysis of the data used in this research is Programming Software SPSS (Statistic Package for the social Sciens) for the windows 29 version. The results of this study indicate that (1) leverage as measured using the Debt To Asset Ratio (DAR) has no positive effect on Return On Assets (ROA); (2) leverage as measured using the Debt To Asset Ratio (DAR) has a positive effect on the activity ratio as measured using Total AIset Turnover (TATO); (3) the activity ratio as measured using Total Asset Turnover (TATO) has no positive effect on profitability as measured using Return On Assets (ROA); (4) activity risk cannot mediate the relationship between leverage and profitability in Property and Real Estate companies listed on the Indonesia Stock Exchange for the 2017-2021 period.